Blockchain-based electronic health record system - Saleh Habtor, Saleh Abdulaziz (2019)
Health records nowadays considered as an important legal document that hold a lot of patients' sensitive information like diseases, medications, personal details and more. The patient's sensitive information is subject to data breaches by hackers on regular basis, also, these patient's records need to be exchanged between different medical institutions that patients visit each time. As a result, the protection of this records in rest and in motion is a must; to preserve patient's privacy and to achieve health record security goals of confidentiality, integrity and availability. The existing health record systems does not have the balance between data privacy, ease of use and secure way to access data, so con icts between data privacy and data accessibility are common to occur. Blockchain works as shared ledger that store each transaction happened in the network, this ledger is immutable, shared and transparent. The blockchain technology provide suitable solution by enables data storage on decentralized platform. This technology can be used in the healthcare domain to provide appropriate access control mechanism and maintain the privacy of health records. In this project, we are proposing a decentralized blockchain-based electronic health record system which also called Decentralized application or DApp in short, that provide an efficient way to access records by health practitioners and maintain confidentiality of patient sensitive information. The system uses Ethereum blockchain and its smart contracts to achieve most secure access control for data security.